REFERENCE EVAPOTRANSPIRATION ESTIMATED BY HARGREAVES-SAMANI IN THE STATE OF CEARÁ, BRAZIL - da Silva, M. G.; Oliveira, I. de S.; do Carmo, F. F.; Lêdo, E. R. F.; da Silva Filho, J. A. (Revista Brasileira de Engenharia de Biossistemas, 2015)
Studies that consider the meteorological aspects of a region, especially, in adequate estimation of the reference evapotranspiration (ETo) can contribute to the optimization of water resources. In this context, in order to evaluate the estimate ETo by HARGREAVES & SAMANI (1985) method compared to the FAO-Penman-Monteith standard method, in climatic conditions of the state of Ceará. The comparison of the values of ETo obtained by FAO-Penman-Monteith standard method and by HARGREAVES & SAMANI (1985) was performed using the standard error of estimate (SEE), the ratio of the averages (ζ) and the index of agreement "d" and performance "c". For the index "c", the highest values were in the localities of Iguatu ("c" = 0.74, "Good"), Jaguaruana and Crateús ("c" = 0.73, "Good") and this estimate may improve with the calibration of HARGREAVES & SAMANI (1985) equation parameters.